Both Major Histocompatibility Complex Class I (MHC-I) and MHC-II Molecules Are Required, while MHC-I Appears To Play a Critical Role in Host Defense against Primary Coxiella burnetii Infection - Buttrum, Laura (Infect Immun, 2018)
To understand the role of class I major histocompatibility complex (MHC-I) and class II MHC (MHC-II) antigen presentation pathways in host defense against Coxiella burnetii infection, we examined whether MHC-I or MHC-II deficiency in mice would significantly influence their susceptibility to virulent C. burnetii Nine Mile phase I (NMI) infection. The results indicate that NMI infection induced more severe disease in both MHC-I-deficient and MHC-II-deficient mice than in wild-type (WT) mice, while only MHC-I-deficient mice developed a severe persistent infection and were unable to control bacterial replication. These results suggest that both MHC-I-restricted CD8(+) T cells and MHC-II-restricted CD4(+) T cells contribute to host defense against primary C. burnetii infection, while MHC-I-restricted CD8(+) T cells appear to play a more critical role in controlling bacterial replication. Additionally, although NMI infection induced more severe disease in TAP1-deficient mice than in their WT counterparts, TAP1 deficiency in mice did not significantly influence their ability to eliminate C. burnetii. This suggests that C. burnetii antigen presentation to CD8(+) T cells by the MHC-I classical pathway may depend only partially on TAP1. Furthermore, granzyme B deficiency in mice did not significantly alter their susceptibility to C. burnetii infection, but perforin-deficient mice were unable to control host inflammatory responses during primary C. burnetii infection. These results suggest that perforin, but not granzyme B, is required for C. burnetii antigen-specific cytotoxic CD8(+) T cells to control primary C. burnetii infection.